Pengaruh Pertumbuhan Kredit pada Profitabilitas dengan Tingkat Perputaran Kredit Sebagai Variabel Pemoderasi pada LPD Kediri - Pramartha, A.A. Ngr. Manik Yuda; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p05, 2018)
LPD health level is an important indicator, and will be able to cultivate public confidence, so people feel safe to save money in LPD either in the form of savings and deposits. This research is a kind of explanatory research that is research that analyze the relationship between one variable with other variable or how a variable influence other variable. Data analysis method used is descriptive method and quantitative method consist of classical assumption test, multiple linear regression test, hypothesis test consist of F-test and t-test, and test of coefficient of determination. Work on data analysis method using SPSS 16.0 for Windows. The data used are primary and secondary data. This research uses 14 LPD as research sample. The results showed that Credit Growth has positive and significant impact on Profitability, Credit rotation rate does not significantly affect Profitability and credit rotation rate does not moderate credit growth to profitability. Keywords: Rate credit turnover, credit growth, profitability.